2012
DOI: 10.1002/aic.13910
|View full text |Cite
|
Sign up to set email alerts
|

A new fragment contribution‐corresponding states method for physicochemical properties prediction of ionic liquids

Abstract: A new fragment contribution-corresponding states (FC-CS) method based on the group contribution method and the corresponding states principle is developed to predict critical properties of ionic liquids (ILs). There are 46 fragments specially classified for ILs considering the ionic features of ILs, and the corresponding fragment increments are determined using the experimental density data. The accuracy of the developed method is verified indirectly via predicting density and surface tension of ILs. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 57 publications
1
92
1
Order By: Relevance
“…[5][6][7] Brennecke's research group 8 first reported that CO 2 showed excellent solubility in IL [bmim] [PF 6 ] in 1999, reaching a 0.72 mole fraction at 313 K and 9.3 MPa. Zhang's research group 9 measured the solubilities of CO 2 in a series of conventional imidazoliumbased tetrafluoroborate ILs.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Brennecke's research group 8 first reported that CO 2 showed excellent solubility in IL [bmim] [PF 6 ] in 1999, reaching a 0.72 mole fraction at 313 K and 9.3 MPa. Zhang's research group 9 measured the solubilities of CO 2 in a series of conventional imidazoliumbased tetrafluoroborate ILs.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, Aspen Plus V8.8 is employed for process simulation and the extended UNIFAC‐IL model is selected for activity estimation. The required information for defining the identified best five IL candidates as pseudo‐components in Aspen Plus (see Supporting Information Table S5) is obtained using the fragment contribution‐corresponding states method proposed by Huang et al For comparison, two continuous extraction processes are designed with ILs and sulfolane as the reference solvent. The corresponding process flow sheets are shown in Figure .…”
Section: Process Evaluation Of Top Il Candidatesmentioning
confidence: 99%
“…The physical properties of ILs, including density, viscosity, surface tension, heat capacity and critical properties, are estimated by a ionic fragment contribution-corresponding states (FCCS) method and the corresponding states principle, and the details is described in our previous work (Huang et al, 2013). The physical properties of ILs, including density, viscosity, surface tension, heat capacity and critical properties, are estimated by a ionic fragment contribution-corresponding states (FCCS) method and the corresponding states principle, and the details is described in our previous work (Huang et al, 2013).…”
Section: Measurement and Simulationmentioning
confidence: 99%